Reduced Growth of Staphylococcus aureus Under High Glucose Conditions Is Associated With Decreased Pentaglycine Expression - Luo, Zhen; Yue, Shan; Chen, Ti; She, Pengfei; Wu, Yuan; Wu, Yong (Frontiers in Microbiology, 2020)
The high-glucose-induced cytotoxicity in diabetes has been widely recognized. Staphylococcus aureus is the most frequent pathogen isolated from diabetic foot ulcers, but the properties of this bacterium under high glucose conditions remain unclear. S. aureus grew in medium usually forms weak biofilm, and which was significantly increased by addition of glucose. However, extracellular DNA (eDNA), an important component of biofilms, was markedly decreased in presence of 15mM glucose. The reduced eDNA content was not caused by degradation, because the nuclease activity of biofilm supernatants with glucose was significantly decreased due to the acidic pH of the medium. Under planktonic state, the growth of S. aureus was significantly decreased in the Luria-Bertani (LB) medium supplemented with 25mM glucose, and reduced growth of S. aureus by glucose was dose-dependent. Except for glucose, the growth of planktonic S. aureus was also markedly decreased by fructose or sucrose. Amounts of acid metabolites were produced under high glucose conditions, but the survival of planktonic S. aureus was unaffected by these acidic conditions. Cells of S. aureus from the culture medium with glucose had a thinner cell wall and highly resistant to lysostaphin compared with the bacteria cultured in LB medium. mRNA expression of genes encoding pentaglycine bridges, the substrate of lysostaphin, was significantly decreased in S. aureus by glucose. In addition to S. aureus, the growth of Staphylococcus haemolyticus and Staphylococcus epidermidis was significantly decreased by an excess of glucose, but strains of Enterococcus faecalis, Escherichia coli, and Pseudomonas aeruginosa were unaffected by glucose. In conclusion, the reduced growth of S. aureus under high glucose conditions is due to impairment of the unique cell-wall structure, pentaglycine bridges.